Antagonistic toxicity of carbon nanotubes and pentachlorophenol to Escherichia coli: Physiological and transcriptional responses. (April 2019) - Deng, Rui; Zhu, Ya; Hou, Jie; White, Jason C.; Gardea-Torresdey, Jorge L.; Lin, Daohui
Abstract: More and more engineered nanoparticles (NPs) are being released into the environment with the accelerated manufacture and use of nanomaterials. The discharged NPs have the possibility of interacting with co-existing contaminants, resulting in joint toxicities that are poorly understood. Here, we investigated the individual and joint toxicities of carbon nanotubes (CNTs), a commonly utilized NP, and pentachlorophenol (PCP), a toxicant, to a model bacterium, Escherichia coli . Bacterial growth inhibition, cell morphology and structure changes, surface properties of CNTs and bacteria, interactions among CNTs, PCP, and bacteria, oxidative stress, and the bioaccumulation of CNTs and PCP were assayed. Transcriptome sequencing (RNA-seq) technology was used to analyze bacterial responses to CNTs and/or PCP in the co-exposure system. As determined by the toxic unit index, co-exposure of CNTs and PCP led to antagonistic toxicity to bacterial growth. The presence of PCP decreased CNT bioaccumulation (9.2 mg/L PCP decreased the accumulated concentration of CNTs by 31.8% compared with 0 mg/L PCP). At the transcriptional level, CNTs attenuated the PCP-induced disturbances of gene expression in biosynthetic, protein metabolic, and small molecule metabolic processes, as well as for organelles. This work is of significance to understanding potential ecological risk of discharged CNTs. Graphical abstract: Image 1